Uma comparação entre a PPP e o enfoque da produtividade na taxa de câmbio de longo prazo - Rebelo, Helene Albuquerque (2014)
The dissertation examines the behavior of the exchange rate in the long term from the perspective of the classical model of purchasing power parity theory (PPP), developed empirically by Cassel and the alternative model proposed by Basso originating from the Marxist benchmark, which emphasizes prices and productivities to determine the exchange rate. The exchange rate behavior is examined for three countries over the 1977-2006 period, with annual frequency. To test the models, it was used the consumer price index (CPI), the GDP, the value-added price index and gross producer price index (EU KLEMS database). The essay uses the causality tests of Johansen, the Dickey-Fuller and Phillips-Perron unit root tests, the VAR (vector autoregression) and VEC (vector error correction) models and performing a projection with the Model Confidence Set. It is ascertained that PPP was not supported for any of the 12 models generated. In Basso s approach, the 48 models generated, cointegration was found in only four models, therefore it is not possible to generalize the new model.